2002
DOI: 10.1007/s10067-002-8275-6
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Histopathological Criteria for Infection in Joint Arthroplasty in Rheumatoid Synovium

Abstract: Intraoperative frozen section is reported to be a reliable means of identifying occult infection for preoperative evaluation of arthroplasty. The aim of this study was to determine whether the reported histopathological criteria--the existence of more than 10 polymorphonuclear cells (PMN) per high-power field--is valuable for determination of infection during the arthroplasty of patients with rheumatoid arthritis (RA). The permanent histological sections of RA synovium were analysed to study the degree of infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Finally, there are two groups of patients in which histology produces a high rate of false positives for diagnosis of infection: patients who undergo a prosthetic replacement and have an underlying inflammatory disease (e.g., rheumatoid arthritis) [ 52 ] and those receiving a prosthetic replacement for a periprosthetic fracture [ 11 , 41 ]. The first group of patients have a persistent neutrophil infiltration in the periprosthetic tissues due to the underlying active disease and not due to prosthetic infection.…”
Section: Types Of Patients Studiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there are two groups of patients in which histology produces a high rate of false positives for diagnosis of infection: patients who undergo a prosthetic replacement and have an underlying inflammatory disease (e.g., rheumatoid arthritis) [ 52 ] and those receiving a prosthetic replacement for a periprosthetic fracture [ 11 , 41 ]. The first group of patients have a persistent neutrophil infiltration in the periprosthetic tissues due to the underlying active disease and not due to prosthetic infection.…”
Section: Types Of Patients Studiedmentioning
confidence: 99%
“…The first group of patients have a persistent neutrophil infiltration in the periprosthetic tissues due to the underlying active disease and not due to prosthetic infection. Kataoka et al [ 52 ] studied synovial tissue in 60 joints from rheumatoid arthritis patients at the time of the placement of an arthroplasty and found 10 cases with more than five PMNs per high-power field. They concluded that PMNs in the rheumatoid synovium were a common microscopic finding and that the presence of more than five PMNs per high-power field in the rheumatoid synovium was not necessarily consistent with infection.…”
Section: Types Of Patients Studiedmentioning
confidence: 99%
“…A causative microorganism was detected in eight joints (Table 1). In the other two joints, the diagnosis was based on the histopathological examination of synovial membrane that showed more than ten granulocytes in a high-power field [8].…”
Section: Methodsmentioning
confidence: 99%